On the diophantine equation x^2 + 5^a 47^b = y^n - Jamal, N. S.; Sapar, S. H.; Johari, M. A. M.; Deraman, F. (Malaysian Mathematical Science Society, 2023)
Diophantine equation is known as a polynomial equation with two or more unknowns which only integral solutions are sought. This paper concentrates on finding an integral to the Diophantine equation x²⁺⁵a∙47b=yn for 0<="" 4.<="" td="" style="box-sizing: border-box;">